Gallium nitride laser diodes with integrated absorber: on the dynamics of self‐pulsation. Issue 3 (24th January 2014) - Holc, Katarzyna; Lükens, Gerrit; Weig, Thomas; Köhler, Klaus; Wagner, Joachim; Schwarz, Ulrich T.
Abstract: The dynamics of self‐pulsation in monolithic multi segment GaN‐based laser diodes (LDs) with integrated absorber, and operating at 410 nm is investigated. The bias‐dependent modal absorption of the devices is determined by high resolution Hakki‐Paoli gain spectroscopy. Using a streak camera detection system we measure the pulsation frequency, applying bias voltages up to –40 V to the absorber section of the multi segment LD. Under moderate reverse voltages, to approximately –15 V, the absorption features a quadratic dependence on the bias voltage with a clear minimum corresponding to the flat band conditions. In this regime we observe stabilized relaxation oscillations, with a pulse repetition rate which depends only on the current in the gain section, but not on the reverse bias in the absorber section. At higher reverse voltages a linear increase of the modal absorption is observed. There, the devices switch to the self‐Q‐switching regime which exhibits a linear decrease of the pulsation frequency with increasing reverse bias. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)